2018
DOI: 10.1155/2018/9370490
|View full text |Cite
|
Sign up to set email alerts
|

Self-Stabilized Precipitation Polymerization and Its Application

Abstract: An effective, value-added use of the large amounts of olefinic compounds produced in the processing of petroleum, aside from ethylene and propylene, has been a long outstanding challenge. Here, we developed a novel heterogeneous polymerization method, beyond emulsion/dispersion/suspension, termed self-stabilized precipitation (2SP) polymerization, which involves the nucleation and growth of nanoparticles (NPs) of a well-defined size without the use of any stabilizers and multifunctional monomers (cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 40 publications
2
79
0
3
Order By: Relevance
“…As can be seen from the aforementioned literature review, the current studies mainly focus on oil droplets in water phase, while the study of water droplets in oil phase is not reported. However, in many engineering fields, especially oil production, oil‐water separation, and oil pollution treatment fields, the motion behavior of water droplets in oil field is more desirable [48–50] . The objective of this work is to fill this gap by finding a smart water droplet micro robot which can go deep into cracks and propel the residual oil out of reservoir.…”
Section: Figurementioning
confidence: 99%
“…As can be seen from the aforementioned literature review, the current studies mainly focus on oil droplets in water phase, while the study of water droplets in oil phase is not reported. However, in many engineering fields, especially oil production, oil‐water separation, and oil pollution treatment fields, the motion behavior of water droplets in oil field is more desirable [48–50] . The objective of this work is to fill this gap by finding a smart water droplet micro robot which can go deep into cracks and propel the residual oil out of reservoir.…”
Section: Figurementioning
confidence: 99%
“…2SP聚合过程中粒子成核-增长过程与常规乳液/ 悬浮/分散聚合存在显著差异, Liu等 [21] 基于热力学及 聚合动力学分析, 并借鉴溶液中小分子结晶过程, 提 出了一种新的成核及增长机理, 如图2所示.…”
Section: Sp聚合成核及增长机理unclassified
“…图 3 2SP聚合过程中微球粒径的自限制和活性增长. (a) 单 位体积样品中PMS粒子数N t 和单个微球中PMS分子链数ξ t 随 反应时间变化曲线; (b) PMS微球体积和粒径分布(PSD)随产 率变化曲线 [21] (网络版彩图) 极大地限制了其实际应用. 陈宇等 [41] 以丁酮/正庚烷 [21] (网络版彩图) Figure 4 Characterizations of the polymer particles produced by 2SP polymerizations.…”
Section: Sp聚合成核及增长机理unclassified
See 1 more Smart Citation
“…It is a long-term research interest of scientists and engineers to synthesize material structures rationally due to different structured materials having different properties and applications [1,2]. Great efforts have been devoted to disclose the formation mechanism of material structures and to develop routes for the rational synthesis [3][4][5].…”
Section: Introductionmentioning
confidence: 99%